School Development in an Effort to Conserve the Environment in the Border Area of Central Java - East Java, Ngawi Regency - Riyadi, Aris (International Research-Based Education Journal, 2021)
The principal is the leader of the school organization. The leadership of the principal is related to the role of influencing his subordinates to always follow his direction in carrying out school administration tasks in the context of developing school organization. In developing school organizations, leaders need to apply an assertive leadership style. Assertive leadership style is defined as the ability to express emotions, defend the truth and maintain interactions with others honestly, responsibly and free from anxiety. This study used content analysis, which is a form of textual analysis that is used to describe and explain the characteristics of the messages in the text. The content analysis allows two approaches, namely qualitative and quantitative. The purpose of this research is to emphasize that in the development of educational organizations, it is necessary to implement assertive leadership.